Knowledge Sharing Ambidexterity in Long-Term Interorganizational Relationships - Im, Ghiyoung; Rai, Arun (Management Science, 2008)
Although past research has investigated the impact of exploration and exploitation on firm performance, there is limited research on these effects in interorganizational relationships. We examine whether the boundary condition for ambidextrous learning can be extended from firms to long-term interorganizational relationships. Specifically, we focus on a particular aspect of learning—namely, explorative and exploitative knowledge sharing—and examine its impact on the performance of long-term relationships. We also theorize how ambidextrous management of the relationship and ontological commitment to span the syntactic, semantic, and pragmatic knowledge boundaries between partners enable knowledge sharing. Our theoretical predictions are tested using data collected from both account managers at customer firms responsible for the relationship with a leading supply chain vendor and account managers at the vendor firm responsible for relationships with customers. The findings suggest that both exploratory and exploitative knowledge sharing lead to relationship performance gains, that such sharing is enabled by the ambidextrous management of the relationship, and that such sharing is facilitated by ontological commitment. Interesting differences in the enablers and consequences of both forms of knowledge sharing are detected between customers and the vendor.